A Web Client Secure Storage Approach in Multi-Cloud Environment - Murtadha Arif Sahbudin; Riccardo Di Pietro; Marco Scarpa (IEEE, 2024)
Date of Conference: 10-12 October 2019 INSPEC Accession Number: 19113501 Conference Location: Rome, Italy